The Effect of Service Quality on Customer Satisfaction at the Gubug Mang Engking Summarecon Bekasi - Bowo Swasono (International Journal of Education, Information Technology, and Others, 2022)
Service Quality aims to provide direction on efforts to improve the company's marketing to maintain customer satisfaction. The purpose of this study was to determine how much influence service quality has on customer satisfaction. Data was collected through questionnaires, sampling was done by means of random sampling which represented the entire population. The method used is descriptive quantitative method. The results of the t test show a significant effect of service quality on customer satisfaction, it is evident that the variable (X) service quality and variable (Y) customer satisfaction has a significant value less than 0.05, namely (0.00 < 0.05), This is evidenced by the significance value in the t-test partially obtained a t-count value of 12.246 while the t-table value is 0.775, so Ho is rejected or Ha is accepted, meaning that service quality affects customer satisfaction.